(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
It is globally accepted that one of India’s most important international role has been the use of its soft power. India’s soft power reflected through her rich cultural heritage. Buddhism and its philosophy have a worldwide appeal, especially in today’s uncertain international scenario. In this paper, we will discuss about the Buddhist philosophy of India and abroad and utilization of India’s Buddhist legacy in terms of Indian foreign policy ranging from Nehru to Modi. While discussing the foreign policy of India based on Buddhism, here the focused area will be on the growing importance of it. Prime Minister Ship of Narendra Modi has started with a much needed change in terms of its Buddhist policy, which is very much remarkable after the era of Nehru. The 21st Century’s India can explore her all avenues of Soft Power to be a potential global super power, following her own legacy as an ancient civilization without imposing cultural imperialism.